Poverty and violence steal the image: New Latin American Cinema in Central America - López Céspedes, Sharon (2022)
In this essay, we take a walk through Central American film production, starting in the 1960s, until the 1980s, in a time marked not only by extreme poverty but also by armed conflicts; period in which the cinema became a powerful tool, playing, most of the time, a propaganda role and, however, under the influence of the New Latin American Cinema, propose a political and revolutionary cinema that benefits from state investment and the international solidarity, in which men and women actively participated by registering the region’s problems with their critical gaze.